OPERATIONAL PERFORMANCE OF AN AGRICULTURAL TRACTOR AS A FUNCTION OF MIXTURE PROPORTIONS AND TYPE OF BIODIESEL - Tavares, Marcos S. [UNESP]; da Camara, Felipe T.; Lopes, Afonso [UNESP]; Pinto, Antonio A. [UNESP] (FapUNIFESP (SciELO), 2022)
The growing demand for clean energy aimed at reducing greenhouse gas emissions associated with the oil crises has encouraged the search for biofuels, among which biodiesel has stood out in the gradual replacement of diesel. This study aimed to evaluate the performance of an agricultural tractor fueled with four types of biodiesels (peanut, sunflower, soybean, and waste frying oil) added to diesel at five proportions (0, 25, 50, 75, and 100% biodiesel, that is, B0, B25, B50, B75, and B100, respectively). The experiment was carried out at the Laboratory of Biofuel and Machinery Testing at FCAV– UNESP. A Valtra BM100 4×2 FWD tractor with a power of 74 kW (100 hp) was used. The drawbar pull force (DF), displacement velocity (V), drawbar power (DP), volumetric fuel consumption (VC), weight fuel consumption (WC), and specific fuel consumption (SC) were studied. The factors did not influence DF, V, and DP. The proportion factor influenced (p<0.01) the volumetric fuel consumption, in which diesel S50 was 14% more efficient than B100. Weight fuel consumption was influenced by the type of biodiesel in the blend. Diesel had the lowest specific fuel consumption (328 g kW h−1). The biodiesel fraction showed a direct relationship with the consumption parameters, with sunflower showing the lowest WC value in the B75 and B100 blends
Keywords: Biofuels; Consumption; Energy; Raw material; Renewable